Gap Analysis and Measurement of Information Technology Readiness for Improvement of Competitive Capabilities to Small and Medium Enterprises in East Java - Andjarwati, T; Hermanto, A; ., Supangat (KnE Social Sciences, 2018)
The growing development of SME sector can be a benchmark for the great potential in improving the economy in East Java. The potential of SMEs will be able to realize a tough and small business, if managed and developed properly. Meanwhile, on the other hand SMEs are also still faced with the problems that lies in the process of administrative and management by utilizing information and communication technology (ICT), thus becoming an obstacle in the development of its business. While at present, for business owners who want to develop their business and able to survive in the competition, one of the efforts that can be done is by utilizing information and communication technology (ICT) as well as having good management capability in managing company’s operational. Therefore, in this study, we conducted a gap analysis and measurement of information technology readiness for SMEs as a way to improve competitive ability. In this research, the method of measuring the level of maturity that we use is BPMM (business process maturity model) and CMMI for SMEs in eastern Java. Based on these measurements, we have also made recommendations for gap improvement in the form of recommendation that can be used by SME owners in improving their organizational skills. It is expected that with the availability of improved forms of organization maturity level can help the competitive ability of existing SMEs in eastern Java in order to continue to grow and it has the ability of continuous improvement. Keywords: Maturity Model, SME, IT Readiness, BPMM